Effects of KST48 [(2R,5SR)3-(2-chlorobenzoyl)-5-(4-chlorophenoxymethyl)-2-(3,4-dichloroph enyl)oxazolidine] on glucose transport in L6 myocytes - Lee, DO; Khil, LY; Chang, TS; Han, HK; Chae, SH; Ahn, MY; Lee, YM; Lee, BH; Jung, JH; Kim, YC; Moon, CK (GEORG THIEME VERLAG KG, 2004)
KST48 [(2R,5SR)3-(2-chlorobenzoyl)-5-(4-chlorophenoxymethyl)-2-(3,4-dichlorophenyl)oxazolidine] is an oxazolidine derivative that showed significant stimulating effects on glucose transport in L6 myocytes. The effects of KST48 on glucose uptake were assayed by measuring the transport of 2-deoxyglucose in L6 myocytes. The translocation of glucose transport-4 (GLUT-4) was examined by western blot analysis. KST48 enhanced glucose transport in a concentration dependent manner and the maximum effect was observed at 50 mumol/L. The stimulation of glucose transport was characterized as the increase in V-max without any significant change of K-m value. This enhanced glucose transport was found to be decreased by the treatment with phenylarsine oxide and genistein, but not by the treatment with wortmannin and tyrphostin 25. KST48 was also proved to increase the GLUT-4 translocation. These results suggest that KST48 increases glucose transport in L6 myocytes by stimulating the translocation of GLUT4 to plasma membrane and this action might be mediated by protein tyrosine kinase but not by phosphatidyl inositol 3-kinase.
Keywords: RAT ADIPOSE-CELL; MUSCLE-CELLS; HEXOSE-TRANSPORT; PLASMA-MEMBRANE; INSULIN; TRANSLOCATION; ADIPOCYTES; ACTIVATION; GLUT4; PHOSPHORYLATION